Identification of Main Obstacles Toward Green Operations on Highway Construction Projects in Cambodia - Sourn, Sonero (การประชุมวิศวกรรมโยธาแห่งชาติครั้งที่ 26, 2021)
Highway construction projects are growing rapidly to reform infrastructure systems in developing countries, resulting in a higher level of pollutions generated from heavy equipment usage and construction operations throughout the project life cycle. The increasing environmentally friendly momentum then drives the construction industry to start adopting green technology to reduce emissions in the community. Nevertheless, the obstacles to the adoption of green technology in highway construction still blocked many contractors to pursue sustainability and contribute their help to the environment in developing countries such as Cambodia. This paper aims to determine the obstacles that prevent contractors to pursue sustainability in the Cambodian highway construction field. 30 lists of factors will be provided under six dimensions of censorious obstacles: funding issue; cooperation and attitude; material resource; government management; time and schedule; and training and knowledge. All 30 factors were identified from a comprehensive literature review. The questionnaire survey will be next developed and applied to interview with professional contractors who have experience in highway construction projects in Cambodia. The result will be collected and analyzed from the total respondents in Cambodia in terms of the descriptive statistic approach to rank the highest critical obstacles among six dimensions. The finding of this paper will help the government to identify the main obstacles to green technology implementation and provide competent solutions for the contractors in Cambodian society towards sustainability.